2020
DOI: 10.2131/fts.7.77
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite inhibits gene expression of perlecan, syndecan-1, -2, -3 and biglycan in cultured vascular endothelial cells

Abstract: Arsenic is an environmental pollutant and is a possible risk factor for vascular diseases such as atherosclerosis. Vascular proteoglycans (PGs) are key molecules in the initiation and progression of atherosclerosis. We previously demonstrated that arsenite, but not arsenate, decreases the synthesis of both heparan sulfate proteoglycans (HSPGs) and chondroitin/dermatan sulfate proteoglycans (CS/DSPGs) in cultured vascular endothelial cells. In the present study, we aimed to identify the PG molecules whose expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Perlecan and biglycan exhibit anti-thrombin activity through the activation of antithrombin III and heparin cofactor II, respectively [ 54 , 55 ]. We previously showed that arsenite inhibits the expression of both perlecan and biglycan in vascular endothelial cells [ 56 , 57 ]. Thus, exposure to arsenite is thought to promote blood coagulation by inducing vascular endothelial cell dysfunction, including inhibition of the production of both t-PA and proteoglycans [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perlecan and biglycan exhibit anti-thrombin activity through the activation of antithrombin III and heparin cofactor II, respectively [ 54 , 55 ]. We previously showed that arsenite inhibits the expression of both perlecan and biglycan in vascular endothelial cells [ 56 , 57 ]. Thus, exposure to arsenite is thought to promote blood coagulation by inducing vascular endothelial cell dysfunction, including inhibition of the production of both t-PA and proteoglycans [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture was performed as described previously (Wu et al, 2020). Briefly, bovine aortic vascular endothelial cells were seeded in six-well culture plates at 2 × 10 4 cells/cm 2 and then cultured for 24, 48, and 72 hr in DMEM supplemented with 10% FBS (10% FBS-DMEM).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%